2021
DOI: 10.3390/antiox10081304
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Antioxidant in Adjunct with Periodontal Therapy in Patients with Type 2 Diabetes: A Systematic Review and Meta-Analysis

Abstract: This review investigated whether the adjunctive use of antioxidants with periodontal therapy improves periodontal parameters in patients with type 2 diabetes. A systematic and extensive literature search for randomized controlled trials (RCTs) conducted before April 2021 was performed on the PubMed, Cochrane Library, and Web of Science databases. The risk of bias was assessed using the Cochrane risk-of-bias tool. A meta-analysis was performed to quantitatively evaluate the clinical outcomes following periodont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 87 publications
(182 reference statements)
0
11
0
Order By: Relevance
“…Thereby, melatonin has been considered a relevant antioxidant, anti-inflammatory, and immunomodulatory function, beyond exerting a powerful endogenous effect as a free-radical scavenger [37], being a key molecule for periodontal protection. In addition, melatonin can protect cells from oxidative stress and neutralize up to ten molecules of reactive oxygen species (ROS), in contrast to classical antioxidants that neutralize only one molecule [38], which can be hypothesized as a reduction of oxidative stress through its application, which would be effective in the treatment of diabetes and periodontal diseases [39]. Moreover, it plays a crucial role in periodontal homeostasis by preventing and preempting periodontal destruction [14,26].…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, melatonin has been considered a relevant antioxidant, anti-inflammatory, and immunomodulatory function, beyond exerting a powerful endogenous effect as a free-radical scavenger [37], being a key molecule for periodontal protection. In addition, melatonin can protect cells from oxidative stress and neutralize up to ten molecules of reactive oxygen species (ROS), in contrast to classical antioxidants that neutralize only one molecule [38], which can be hypothesized as a reduction of oxidative stress through its application, which would be effective in the treatment of diabetes and periodontal diseases [39]. Moreover, it plays a crucial role in periodontal homeostasis by preventing and preempting periodontal destruction [14,26].…”
Section: Discussionmentioning
confidence: 99%
“…A randomized controlled clinical trial showed that melatonin significantly enhanced the antioxidative capacity (TAC) and inhibited the MMP-9 levels in GCF [ 98 ]. A meta-analysis of two RCTs revealed that in periodontitis patients with diabetes, combined NSPT with melatonin remarkably reduce the periodontal pocket depths, with reference with NSPT alone [ 125 ]. In gingival fibroblast from Wistar rats, glutamate (GLUT) and DL-buthionine sulfoximine (BSO) treatment lead to the production of superoxide anion and cell apoptosis, which can be totally counteracted by melatonin [ 10 ].…”
Section: Melatonin: Biological Functions and Beneficial Effects On Pe...mentioning
confidence: 99%
“…Moreover, systemic administration or topical application of melatonin alleviates the inflammatory condition and improves periodontal status in diabetes patients with periodontitis [ 102 , 103 , 150 ]. Periodontal pocket depths were significantly reduced when combining melatonin with NSPT in periodontitis patients with diabetes [ 125 ].…”
Section: Melatonin and Periodontitis-related Systemic Diseases: Far M...mentioning
confidence: 99%
“…Diabetes has been known to affect cells in periodontal tissue, such as fibroblasts [34,35], osteoblasts, and osteoclasts, to enhance the destruction of periodontal tissue that accompanies inflammation [36,37]. Diabetes might lead to the progression of periodontitis by modifying the host response to local inflammation [38].…”
Section: Plos Onementioning
confidence: 99%